Ejecución presupuestaria de los gastos del GAD Parroquial Rural de la Unión, en el periodo 2020. - Masacon Salvatierra, Blanca Alexandra (2022)
The identified problem that gives rise to the subject of study is based on the constant variations and modifications that exist in the budgetary execution of the La Unión Parish GAD, which causes it to end up spending more resources than originally planned, allocating more resources to certain items. budgetary measures that are not taken advantage of or used properly, or on the contrary, that are not assigned sufficient values to certain items, for these reasons the proposed objective is to analyze the budgetary execution of the expenses of the rural parish GAD La Unión, in the 2020 period. As a research methodology, the descriptive method was chosen, because it turned out to be the most appropriate, in such a way that it allowed describing the problematic situation and the results obtained, which are based on the analysis of budget execution, information that was collected from the application of research techniques, such as bibliographic research, which provided sufficient theoretical support to carry out the analysis of the Expenses of the La Unión Rural Parish GAD. Among the conclusions and results that it was possible to reach, it is found that, as a result of the reforms carried out in the different items of the expenditure budget cell, there are variations in the expenses presented in the budget cell, which are products of the reforms. implemented in the year 2020, which meant a decrease in the expenses of the La Unión Rural Parish GAD in certain items, as well as an increase in other types of expenses.